The Aura of Eccentricity: Reflections on Outsider Art Rhetoric and its Impact on a Critical Discourse - Kramer, Cortney Anderson (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2018)
In the field of Art History, affecting art with the artist’s aura is a central mechanism of canon creation that mythologizes artists into objects of desire. This tendency permeates outsider art whose appeal is rooted in biographical exceptionalism and eccentricity rather than aesthetic aptitude (see Morgan 2018). Reviewing the work of Henry Darger, Eugene Von Bruenchenhein, and A.G. Rizzoli—artists whose works are accumulative, some suggest compulsive, in reiteration and magnitude—this essay explores the pitfalls of projecting an aesthetic affect onto the artist and in turn building their value upon a fabricated aura of eccentricity. The aura of eccentricity resides at the nexus between material and idea. It is both real and mythologized, materially communicated through excess, opulence, and exaggeration of shapes, scale, colour, and medium yet ideologically created in the realm of differentiating adjectives and semantic flourishes. Engaging with Walter Benjamin and Theodor Adorno, this essay argues that material culture demands self-awareness of our own interpretive prejudices, in this case fashioning the artist outsider with eccentric narratives retroactively projected upon them through the interpretation of their work.